Typical peruvians idioms in the literary works of Mario Vargas Llosa - Lovón Cueva, Marco Antonio (2012)
This article contains the typical Peruvian idioms used by the Nobel Prize winner Mario Vargas Llosa in his works The Time of the Hero, Aunt Julia and the Scriptwriter, Conversation in The Cathedral, Death in the Andes, Captain Pantoja and the Special Service, The Cubs and Other Stories, in order to highlight its value within the Peruvian lexicon heritage. The terms employed by Vargas Llosa, remain in force in different levels of use. Strategically, we will classify the terms according to word categories: nouns, adjectives and verbs. According to the lexical analysis, the names or nouns are the most used in his literary writings. In the name article, we will collect a series of complex expressions present in his works. This compilation shows that verbal locutions are the most recurrent forms of expressiveness of Peruvian speech.